Devising a procedure for justifying the need for samples of weapons and weapon target assignment when using a reconnaissance firing system - Maistrenko, Oleksandr; Khoma, Vitalii; Lykholot, Oleksandr; Shcherba, Andrii; Yakubovskyi, Oleksandr; Stetsiv, Stanislav; Kornienko, Alexander; Savelіev, Andrii (Eastern-European Journal of Enterprise Technologies, 2021)
This paper proposes an algorithm to substantiate the need for weapons samples, as well as targeting when using a reconnaissance firing system taking into consideration the peculiarities of functioning of such systems. The algorithm essentially implies streamlining the stages in determining the magnitude of the reduction of the enemy's combat potential and, on its basis, the formation of the need for the number of weapons by type. The algorithm makes it possible to take into consideration the nonlinearity of functions that describe both different types of weapons and targets. In addition, this algorithm is based on a modified method of nonlinear programming (two functions). The modification involves the use of a normalized share of the weight of each target as weight coefficients. This allows for targeting while taking into consideration the established level of the combat potential of an enemy. A procedure for determining the need for samples of weapons and targeting in the use of reconnaissance firing systems has been devised. It was determined that in order to achieve the goal of enemy fire damage, it is not typically necessary to use all weapons samples. In general, the procedure makes it possible to take into consideration the peculiarities of the samples of weapons and their suitability to hit a certain target. That could prevent problems with overspending of resources, failures in the detection-defeat cycle, non-fulfillment (not fully performing) tasks during enemy fire damage. In general, the algorithm and procedure for determining the need for the samples of weapons and targeting when using a reconnaissance firing system testify to devising a methodology for justifying the need for weapons samples and targeting. The performance and adequacy of this procedure have been tested by considering an example of determining the need for weapons samples and targeting and obtaining the result confirmed by the experience in the use of reconnaissance firing systems